ASPEK HUKUM DALAM PENYELESAIAN SENGKETA PERDATA MELALUI MEDIASI DI PENGADILAN NEGERI SORONG - Bakarbesy, Yohan; Renouw, Dian Mega Erianti; M. Syauta, Novalin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Mediation is one way for parties to resolve disputes amicably. The advantage of mediation is that if the parties can reach an agreement, the dispute is considered resolved so that it does not require a follow-up trial which of course will require a long time and costs a lot of money. Judge at Sorong District Court in resolving civil lawsuits in accordance with Perma No. 1 of 2016, recommends the parties to discuss through mediation, some are successful but most are unsuccessful. The purpose of this writing is to find out the resolution of civil disputes through mediation at the Sorong Class IB District Court and to find out the obstacles in resolving civil disputes through mediation at the Sorong Class IB District Court.The method used in this research is, the type of research is normative empirical, the type and source of data used is primary and secondary data, data collection techniques are through literature study, interviews and documentation and the data analysis technique used is descriptive qualitative.The results of the research are, Settlement of civil disputes through mediation at the Sorong Class IB District Court, as is done in other district courts, which follows PERMA No. 1 of 2016. Even though there are many lawsuits, there is little possibility of mediation between the parties, but in accordance with existing regulations, the judge at the beginning of the trial always gives the parties the opportunity to discuss and resolve obstacles in resolving civil disputes through mediation at the Class IB District Court. Pushing, namely, lack of cooperation between the parties during deliberations and the parties prioritize their own desires Keywords: Mediation, District Court, Civil Lawsuit